Catalase and sodium fluoride mediated rehabilitation of enamel bleached with 37% hydrogen peroxide - Ruchi Thakur; Anand L Shigli; Divya Sharma; Gagan Thakur (Wolters Kluwer Medknow Publications, 2015)
Background: Bleaching agents bring about a range of unwanted changes in the physical structure of enamel which needs to be restored qualitatively and timely. Catalase being an antioxidant ensures the effective removal of free radicals and improvement in fluoride mediated remineralization from the enamel microstructure which if retained may harm the integrity and affect the hardness of enamel. Materials and Methods: Thirty freshly extracted incisors were sectioned to 6 slabs which were divided into 5 groups: Group A, control; Group B, treatment with 37% hydrogen peroxide (HP); Group C, treatment with 37% HP and catalase, Group D, treatment with 37% HP and 5% sodium fluoride application, Group E, treatment with 37% HP followed by catalase and 5% sodium fluoride. Scanning electron microscope and microhardness analysis were done for all slabs. One-way ANOVA test was applied among different groups. Results: Vicker's microhardness number (VHN) of Group B and C was significantly lower. No significant difference between VHN of Group B and C. VHN of Group D was significantly higher than Group A, B, and C; but significantly lower than Group E. VHN of Group E was significantly higher than any other experimental group. One-way ANOVA revealed a highly significant P value (P = 0.0001) and so Tukey's post-hoc Test for the group comparisons was employed. Conclusion: Subsequent treatment of bleached enamel with catalase and fluoride varnish separately results in repairing and significantly increasing the microhardness.